Les Philosophés kurun ke-18 di Perancis: sifat-sifat reaksioner di sebalik bayang revolusioner - Azmi Arifin, (Penerbit UKM, 2010)
The Philosophés and Enlightenment were thought to play an important role in the French Revolution of 1789. They were claimed to champion radical demands for equality and democracy for the people, thus challenging the prevailing aristocratic order. It was even said that without them, the French would have not achieved political enlightenment and the revolution of 1789 might not had happened. This writing, however, questions the validity of that perception. What were the true roles of the philosophés in the revolution? Were the ideas and goals of the movement radical in the context of politics and culture of France in 18th century? This study discovered that there are solid proofs that shows that, far from championing the principles of democracy and equality for the people, the philosophés was really a movement of elites, conservatives and reactionaries, who fought to defend and further strengthening the institutions of aristocracy and monarchy in France until the revolution.